6p=p-40

Simple and best practice solution for 6p=p-40 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6p=p-40 equation:


Simplifying
6p = p + -40

Reorder the terms:
6p = -40 + p

Solving
6p = -40 + p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-1p' to each side of the equation.
6p + -1p = -40 + p + -1p

Combine like terms: 6p + -1p = 5p
5p = -40 + p + -1p

Combine like terms: p + -1p = 0
5p = -40 + 0
5p = -40

Divide each side by '5'.
p = -8

Simplifying
p = -8

See similar equations:

| (4x^2)+37x+75=0 | | z^2+13z+36=0 | | X^2-8x+84=0 | | 3x-10=2x+18 | | -x-24=5+x | | -18d+5d(8+3d)=7(3d-8) | | 5+r=18 | | 16-9(d-5)=-2 | | -148=4(6+7x)-4 | | c+5=41 | | 24=2x+3(2x) | | 5.8=-8+x | | 6(x+4)-5=1 | | 3+5w=9+4w | | -2x+2=-2x+1 | | 7=n/7+9 | | 2n^2-3n+4=0 | | (9x^2)-131x+450=0 | | -3(y-6)=30 | | 2y+x=-9 | | Y+11=-11 | | 5-x-1=x-2 | | Y+11=11 | | 11=3n-10 | | -29x+2=-2x+1 | | -7(b+3)=7 | | (x+18)(x-6)=25 | | 3b-1(6-b)=22 | | x+3x=50000 | | 2r=72 | | 2(x+4)=4+4x | | Z^2-2z-24=0 |

Equations solver categories